Smart pictorial dictionary via mobile augmented reality - Nurul Asyiqin Khazali; Ismassabah Ismail; Norzehan Sakamat; Nurul Hidayah Mat Zain; Nor Azida Mohamed Noh; Norshahidatul Hasana Ishak (Institute of Advanced Engineering and Science, 2023)
Augmented reality (AR) technology offers many benefits for language teaching and learning. Using the AR technique in pedagogy attracts and engages children to learn and memorize easily, even in a short time. Visual representation learning method like a pictorial dictionary is one of the beginnings of learning for children. It helps children to visualize the object and memorize it in effective ways. Based on the survey conducted in one of the primary schools at Merlimau, Melaka, it was found that the children have difficulties in learning English. The development of pictorial dictionaries with the combination of AR technology in 3D that are presented in the form of mobile applications can be used to improve existing learning methods in English. The method used during the development of this application is the ADDIE model, which comes with five phases: analysis, design, development, implementation, and evaluation. The development of the ‘smart pictorial dictionary via mobile AR application has been done successfully and has received positive results. Based on the evaluation using the attention relevance confidence satisfaction (ARCS) model, the output has an overall mean of 4.58, which shows that using AR technology in early childhood learning makes children learn more.